PC.74 The importance of testing for Respiratory Syncytial Virus (RSV) in infants presenting with bronchiolitis who are receiving palivizumab. (9th June 2014) - Sullivan, CL; Morgan, C
Abstract : Introduction: Bronchiolitis is a significant cause of respiratory morbidity and hospital admission particularly for ex-preterm infants. Respiratory Syncytial Virus (RSV) is the commonest responsible organism (80%). RSV detected by a molecular test on a nasopharyngeal swab, has a sensitivity and specificity around 97%. Many very high risk infants e.g. those with neonatal chronic lung disease (nCLD) on home oxygen receive monthly humanised monoclonal antibody prophylaxis against RSV (palivizumab) yet still develop bronchiolitis. Palivizumab is a costly treatment therefore it is important to document if RSV causes these admissions. Many UK centres only test for RSV at the start of the season, we test for the whole period. Method: Infants who were eligible for palivizumab, according to national guidelines, received monthly injections for the 2013–2014 season. All admissions for clinical bronchiolitis were recorded prospectively including results of the viral molecular tests. Results: 23 infants in our health board received palivizumab for the 2013–2014 bronchiolitis season. There were 10 admissions for bronchiolitis in 8 of the infants receiving palivizumab, 35% (8/23). In none was the swab positive for RSV, 3 were positive for rhinovirus and in the remainder no virus was identified. No infant required intensive care. Conclusion: Despite an admission rate of 43% (10/23) with bronchiolitis in this high risk group, not one infant had infection due to RSV as detected by the molecular test. Due to the high financial cost of omalizumab treatment in prevention of RSV infection, off-set by reduction in RSV admissions, this documentation is important for on-going financial support of this treatment for these vulnerable infants.